Pastor Sebagai Teolog di Dalam Komunitas Kristen - Clement Hiu (Sekolah Tinggi Teologi Aletheia, 2023)
Abstract:The role of the pastor as a theologian is getting eroded. This can be seen in the ministry of pastors who do not prioritize preaching the word of God, do not think critically about contemporary issues and do not contribute to scholarly work. As a result, the teaching in the church weakens, the congregation’s spiritual needs are not satisfied, and the people’s faith is shallow. In the end, church growth will become stagnant and will be displaced by the changing world. Therefore, the pastor must be faithful to his role as a theologian for the Christian community. Pastors need to realize their calling as theologians and find out where the Christian community is the burden of their ministry as theologians. To carry out his vocation as a theologian, the pastor should equip himself with the correct method of theology; achieve biblical, cultural and human literacy; and apply the four spheres of theological scholarship, namely research, systemization, ecclesial significance articulation and ecclesial implementation. In realizing his role as a theologian, the pastor should return to his ministerial focus as a preacher of God’s word and rethink his pastoral ministry. And considering the breadth of theological scholarly disciplines, pastors need to collaborate with qualified colleagues or institutions to produce theological scholarly works. Abstrak: Peranan pastor sebagai teolog semakin terkikis. Hal ini terlihat dari pelayanan para pastor yang tidak mengutamakan pemberitaan firman Tuhan, tidak berpikir kritis terhadap isu-isu kontemporer dan tidak adanya sumbangsih mereka dalam karya ilmiah. Akibatnya, pengajaran gereja menjadi lemah, kebutuhan rohani jemaat tidak terpenuhi dan dangkalnya iman jemaat. Pada akhirnya, pertumbuhan gereja akan menjadi stagnan dan akan tergusur oleh perubahan zaman. Karena itu, pastor harus setia pada peranannya sebagai teolog bagi komunitas Kristen. Pastor perlu menyadari panggilannya sebagai teolog dan menemukan di mana komunitas Kristen yang menjadi beban pelayanannya sebagai teolog. Untuk menjalankan panggilannya sebagai teolog, pastor hendaknya memperlengkapi diri dengan metode berteologi yang benar; mencapai literasi biblikal, budaya dan manusia; serta menerapkan empat bidang keilmuan teologi, yaitu penelitian, sistematisasi, artikulasi signifikansi gerejawi dan implementasi gerejawi. Dalam mewujudnyatakan peranannya sebagai teolog, pastor hendaknya kembali kepada fokus pelayanannya sebagai pemberita firman Tuhan dan memikir ulang pelayanan pastoralnya. Dan mengingat luasnya disiplin keilmuan teologi, maka dalam usaha menghasilkan karya ilmiah yang teologis, pastor perlu berkolaborasi dengan rekan atau institusi yang mumpuni.